The process of curriculum change in the Philippine Science High School, 1968-1970 description and analysis - Alcid, Carmelita V.; Elequin, Eleanor T. (Quezon City College of Education, University of the Philippines Diliman, 1972)
The Philippine Science High School was enacted into law on June 22, 1963. The researcher attempted to descriptively analyze the ecological forces which propelled curriculum change in the school and the process of curriculum change. In the 1969 process of curriculum change, there were four stages, while there were six stages in the 1970 curriculum revision process. These changes were subject changes, time change, period change, credit change and year change. The reasons for the institutioned changes in the 1969 modified 5-year curriculum were the following: systematization of course offerings, correlation with the Bureau of Public Schools' requirements for graduation, articulation with the university and with other secondary schools, the Filipinization movement and the student aspirations.
Thesis (M.A. in Education - Curriculum Studies)--University of the Philippines, Diliman
Keywords: Philippine Science High School -- Curricula; Curriculum change -- Philippines; Education, Secondary -- Philippines